The mummy under the bed : essays on gender and methodology in the ancient Near East - Gender, Methodology and the Ancient Near East (Workshop) 2019 : Koninklijke Vlaamse Academie voor Taal- en Letterkunde); Graef, Katrien de; Garcia-Ventura, Agnès; Goddeeris, Anne; Nakhai, Beth Alpert, 1951- (Münster, Germany : Zaphon, 2022)
"The present volume contains 17 contributions devoted to various methodological approaches to gender studies within the broad field of Ancient Near Eastern studies, including ancient history, archaeology, art history, Assyriology, Phoenician-Punic studies, and biblical studies. This collection is the result of presentations, exchanges, and discussions that took place during the third workshop on Gender, Methodology, and the Ancient Near East in Belgium from 8 to 10 April 2019. Over these three days, scholars from the four corners of the world descended on the Royal Academy of Dutch Language and Literature in the picturesque city of Ghent in order to exchange research findings, ideas, and hypotheses on gender-related topics within the realms of greater Mesopotamia, Egypt, and the Levant"-- Page 7.
Preface and acknowledgements : Some words with a mummy -- Women talking about women : excavating the memory of women in Ancient Near Eastern studies / Agnès Garcia-Ventura -- 1. Reading against the grain. The Late Bronze Age in Syria : was it a dark age for women? / Frances Pinnock -- The female gaze : the subjected body in Tablet 103 of Šumma ālu Omens 1-7 / Ann K. Guinan -- In nomine matris et filii . . . The use of matronymics in the legal and economic documents from Sukkalmaḫ Susa / Katrien De Graef -- 2. Cult and cults. Women in cult in first millennium BCE Mesopotamia / Natalie Naomi May -- Engendered cosmic regions in ancient Mesopotamian mythologies / Lorenzo Verderame -- Of cities, mothers, and homes : a cognitive-stylistic approach to gendered space in the Hebrew Bible / Karolien Vermeulen -- Vanishing point : new perspectivity on women in the Book of Exodus / Elizabeth B. Tracy -- 3. Ancient beauties. The aroma of majesty : gender and the Hebrew Bible's olfactory cultic theology / Anne Katrine de Hemmer Gudme -- Performing beauty in Phoenician-Punic cultures : a gender perspective / Meritxell Ferrer, Mireia López-Bertran -- Embodying the past : the case of the Goddess on Lion at Hasanlu / Letteria Grazia Fassari, Raffaella Frascarelli -- Entangled at death : beads, gender, and life cycles during the Central Anatolian Early Neolithic ; Aşıklı Höyük as a case study / Sera Yelözer, Mihriban Özbaşaran -- 4. Networks and powers. Zinu, wife and manager in Old Babylonian Larsa / Baptiste Fiette -- Grandmother's tablets : some reflections on female landowners in Nuzi / Brigitte Lion -- Women and their weight : incorporating weighted edges in a network analysis of the central redistributive household of Nippur (eighteenth century BCE) / Anne Goddeeris -- Women's property and social networks in Mesopotamia / Allison Thomason -- Was it law? Gender relations and legal practice in the Ancient Near East / Ilan Peled.
Includes bibliographical references and index.
Texts primarily in English with some Hebrew text and translations.
Print version record.
JSTOR
Keywords: Gender identity -- Middle East -- Congresses; Sex role -- Middle East -- Congresses; Women -- Middle East -- Congresses; Bronze age -- Middle East -- Congresses; Mythology, Assyro-Babylonian -- Congresses; Women -- Mythology -- Congresses; Bible and feminism -- Congresses; Femininity in the Bible -- Congresses; Goddesses, Phoenician -- Congresses; Mythology, Phoenician -- Congresses; Mythologie assyro-babylonienne -- Congrès.; Femmes -- Mythologie -- Congrès.; Bible et féminisme -- Congrès.; Déesses phéniciennes -- Congrès.; Mythologie phénicienne -- Congrès.; HISTORY / Ancient / General; Bible and feminism; Bronze age; Femininity in the Bible; Gender identity; Goddesses, Phoenician; Mythology, Assyro-Babylonian; Mythology, Phoenician; Sex role; Women; Women -- Mythology; Middle East; Gender roles; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.